Prokka: rapid prokaryotic genome annotation - Seemann, Torsten (Bioinformatics (Oxford, England), 2014)
The multiplex capability and high yield of current day DNA-sequencing instruments has made bacterial whole genome sequencing a routine affair. The subsequent de novo assembly of reads into contigs has been well addressed. The final step of annotating all relevant genomic features on those contigs can be achieved slowly using existing web- and email-based systems, but these are not applicable for sensitive data or integrating into computational pipelines. Here we introduce Prokka, a command line software tool to fully annotate a draft bacterial genome in about 10 min on a typical desktop computer. It produces standards-compliant output files for further analysis or viewing in genome browsers. Availability and implementation: Prokka is implemented in Perl and is freely available under an open source GPLv2 license from http://vicbioinformatics.com/ . Contact:  torsten.seemann@monash.edu